2019
DOI: 10.1017/s000711451900031x
|View full text |Cite
|
Sign up to set email alerts
|

Whole grain, bran and cereal fibre consumption and CVD: a systematic review

Abstract: Whole grain intake is associated with lower CVD risk in epidemiological studies. It is unclear to what extent cereal fibre, located primarily within the bran, is responsible. This review aimed to evaluate association between intake of whole grain, cereal fibre and bran and CVD risk. Academic databases were searched for human studies published before March 2018. Observational studies reporting whole grain and cereal fibre or bran intake in association with any CVD-related outcome were included. Studies were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…Potential benefits of the diet have been hypothesised to be due to the diets nutrient profile with high levels of fibre (54) , calcium (55) , magnesium (56) , potassium, low sodium (57) and sugar (58) . The potential mechanisms of action between the individual components of the DASH diet pattern and cardiometabolic health have been extensively described in a recent review (59) .…”
Section: Discussionmentioning
confidence: 99%
“…Potential benefits of the diet have been hypothesised to be due to the diets nutrient profile with high levels of fibre (54) , calcium (55) , magnesium (56) , potassium, low sodium (57) and sugar (58) . The potential mechanisms of action between the individual components of the DASH diet pattern and cardiometabolic health have been extensively described in a recent review (59) .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that it is through their high dietary fibre levels that these whole grain products play a very important role in the prevention and alleviation of NCDs. The term ‘whole grain products’ refers to products that are made with a relative proportion of bran, germ and endosperm tissue equal to what would naturally occur in intact grains [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These methods have the potential to misestimate true whole grain intake, which confounds results and makes it difficult to accurately determine if findings can be attributed specifically to whole grains. We recently reviewed existing observational studies exploring whole grains, bran and cereal fibre and the risk of CVD and CVD-related outcomes (15) . We found that when studies defined whole grains as including the germ, endosperm and bran in their natural proportions, results were stronger and less likely to be attenuated after adjusting for individual whole grain components such as cereal fibre intake, potentially due to poorer-quality non-whole grain foods weakening any associations.…”
mentioning
confidence: 99%